How Severe Plastic Deformation Changes the Mechanical Properties of Thermoelectric Skutterudites and Half Heusler Alloys - Rogl, Gerda; Rogl, Peter F. (Frontiers in Materials, 2020)
Thermoelectric leg materials with a high figure of merit, ZT, are the essential basis to build thermoelectric generators, directly converting waste heat into electricity. Skutterudites and half-Heusler alloys are promising candidates because they can be used in a wide temperature range, the starting material is available and cheap and in addition they are environmentally friendly. Severe plastic deformation via high-pressure torsion (HPT) is a technique to achieve very fine grains in micro- or even nano size with small and high angle grain boundaries and in parallel introduces a high level of defects like vacancies and dislocations. Therefore, this method was applied not only to enhance ZT of ball-milled and hot-pressed skutterudites and half-Heusler alloys but so far was also successful to directly produce dense nanostructured bulks from skutterudite powders. Although HPT compacted samples are chemically homogeneous, they are not homogeneous with respect to the shear strain increasing from the center to the rim. HPT changes the microstructure and density and thereby not only influences the thermoelectric but also the mechanical properties. In this work an overview is given of the influence of HPT on hardness, elastic moduli, indentation fracture toughness, thermal expansion and thermal shock resistance. The corresponding properties of hot-pressed skutterudites and half-Heusler alloys are compared with those after severe plastic deformation, dependent on the processing properties and position of the specimen in respect to shear strain. Data are collected from earlier investigations of the authors and from the literature, but also newly achieved and evaluated data are included.